The environmental conditions determine the roughness of the skin of the avocado ‘Hass’ fruit - Álvarez Bravo, Arturo; Salazar García, Samuel (Revista Mexicana de Ciencias Agrícolas, 2017)
One of the characteristics of the skin of the avocado ‘Hass’ is the roughness; however, little has been studied about this feature. The objective of this work was to quantify the roughness, in different sections of the skin and development stages of avocado ‘Hass’ fruits, harvested in three contrasting climates of western Mexico. The study was carried out from March to November 2015. Fruits were collected in three ‘Hass’ producing regions of western Mexico with different types of climate (warm subhumid, subhumid and warm temperate). A geographic information system and spatial analysis techniques were used to quantify the roughness of the ventral lateral, upper dorsal frontal and ventral frontal equatorial sections of the fruit. Temperature and precipitation were recorded monthly in the three producing regions. The warm subhumid climate was the warmest while the driest was the sub-humid and the rainy temperate. The degree of roughness showed differences between regions (climates), sections of the skin and stages of development of the fruit. The fruits produced in warm subhumid climate showed greater roughness and those of temperate climate the lower roughness. The degree of roughness of the avocado ‘Hass’ skin is influenced by the environmental conditions where the fruit develops, which can evidence the genetic plasticity of this avocado cultivar.
Keywords: Persea americana , fruit development, ecophysiology